2007
DOI: 10.1002/ccd.21277
|View full text |Cite
|
Sign up to set email alerts
|

Day procedure intervention is safe and complication free in higher risk patients undergoing transradial angioplasty and stenting. The discharge study

Abstract: Day case transradial percutaneous intervention with a 6-hr period of post procedure observation is a safe and feasible practice. The presence of higher-risk features should not be considered an absolute indication for overnight admission in patients considered clinically appropriate for discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 11 publications
4
28
0
2
Order By: Relevance
“…While OPD TRI has been shown to be feasible and safe in Western studies, [5][6][7][11][12][13][14][15][16][17][18] the situation in Asia is unclear. The present prospective nonrandomized comparison study involving acceptably large numbers of patients provides an indication that, by careful selection criteria, same-day discharge after OPD TRIs is acceptable and without serious PCI related complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While OPD TRI has been shown to be feasible and safe in Western studies, [5][6][7][11][12][13][14][15][16][17][18] the situation in Asia is unclear. The present prospective nonrandomized comparison study involving acceptably large numbers of patients provides an indication that, by careful selection criteria, same-day discharge after OPD TRIs is acceptable and without serious PCI related complications.…”
Section: Discussionmentioning
confidence: 99%
“…4) Accordingly, TRI has been increasingly adopted for out-patient department (OPD) procedures, with same-day discharge, with a variety of studies including randomized trials verifying the safety and feasibility of the approach in Western countries. [5][6][7][12][13][14][15][16][17][18][19][20] Beginning in 1994, we and others introduced TRI in Asia. [8][9][10] However, feasibility and safety issues of OPD TRI without admission have not been reported in Asia.…”
mentioning
confidence: 99%
“…Two published meta analyses have previously described at least equivalent revascularisation results using either approach with radial access having significant lower bleeding complications whilst at the cost of higher technical failure rates [8,9]. In a series of over 1000 transradial PCI's, Small et al [10] confirmed that all post procedure complications could be and were identified within six hours of the procedure with complications between six and 24 hours being exceedingly rare. Despite this published data there has remained a general reluctance to discharging patients on the day of the procedure.…”
Section: Introductionmentioning
confidence: 87%
“…This clearly impacts the patient's length of hospital stay, thus increasing occupied bed days, and health care expenditure [23]. …”
mentioning
confidence: 99%